Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Terhadap Hasil Belajar Siswa Pada Subtema 3 Pengaruh Kalor Terhadap Kehidupan Kelas V SD Negeri Percontohan Pematang Siantar - Stefani Philia Turnip; Lisbet Novianti Sihombing; Desi Sijabat (Journal on Education, 2023)
The purpose of this study was to determine the effect of the Teams Games Tournament (TGT) Learning Model on Student Learning Outcomes in Sub-theme 3 Class V The Effect of Heat on Life at Pilot Pematangsiantar Elementary School. This research is a quantitative study with the type of Pre-Experimental Design with a One Group Pretest research design. -Posttest (Initial Test-Final Test in a single group). In this study only used one research class. The sample for this study was class V, totaling 30 students. The sampling technique using saturated sampling is a sampling technique when the population is used as a sample. Based on the results of data analysis and hypothesis testing that has been done, that the effect of the Teams Games Tournament (TGT) learning model on student learning outcomes. It can be seen that the acquisition of significant value (2-tailed) is less than 0.05 (0.00 <0.05 ) and the value of tcount is greater than ttable (13.152 > 2.048.) then H0 is rejected and Ha is accepted. So it can be concluded that the Teams Games Tournament (TGT) learning model has an effect on student results in class III sub-theme 1 of Pilot Public Elementary Schools